Cortical beta power reflects decision dynamics and uncovers multiple facets of post-error adaptation - Adrian G. Fischer (Nature Portfolio, 2018)
People slow down reactions after errors, yet it is debated whether the mechanisms behind this slowing are beneficial for future performance. Here, the authors show that EEG measures converge with model predictions supporting a complex but overall beneficial mechanism of post-error slowing.